Cell Surface Display of a Single-Chain Antibody for Attaching Polypeptides. (October 1996) - Rode, H.-J.; Little, M.; Fuchs, P.; Dörsam, H.; Schooltink, H.; Inés, C. de; Dübel, S.; Breitling, F.
To provide an efficient means of coupling proteins, peptides and other suitable moieties to cells, we have constructed a retroviral expression vector for cell surface display of a single-chain antibody (scFv) against the hapten 4-ethoxymethylene-2-phenyl-oxazoline-5-one (phOx). The hapten phOx can be easily conjugated to primary amino and sulfhydryl groups, thus providing points of attachment for the cell surface-bound antiphOx scFv. This universal cell coupling system could prove to be particularly useful for anchoring monoclonal antibodies for tumor targeting and to present co-stimulatory molecules and other ligands (even mixtures) at the cell surface for gene therapy.